Putting order into literal and figurative uses of verbs: "Romper" as a case study - Spalek, Alexandra (Borealis – An International Journal of Hispanic Linguistics, 2012)
This paper argues in favor of the hypothesis that the so-called ﬁgurative and literal meanings of verbs share a common core meaning that constitutes the semantic base of verbs across contexts. I argue for an underspeciﬁcation model of the lexicon and take the Spanish change of state verb romper ‘break’ as a case study. It is shown that the meaning variation of romper-VPs is correlated with the semantics of the theme in two ways: 1) whether and how exactly the theme is affected by the change and 2) whether the theme has a simple or a complex mereological structure. I thus analyze romper in terms of a simple scalar change, for which the exact dimension of change depends on the properties of the theme argument. The study is taken as precursor for the analysis of lexical entailments of change of state verbs in composition and aims at showing that what has often been denominated metaphoric extensions or non-regular polysemy can be analyzed alike through an underspeciﬁcation approach. The present paper represents a view of lexicon that goes against a trivial and static conception of lexical meaning.